Development of reconfigurable distributed embedded systems with a model‐driven approach. (23rd July 2013) - Krichen, Fatma; Hamid, Brahim; Zalila, Bechir; Jmaiel, Mohamed; Coulette, Bernard
Summary: In this paper, we propose a model‐driven approach allowing to build reconfigurable distributed real‐time embedded (DRE) systems. The constant growth of the complexity and the required autonomy of embedded software systems management give the dynamic reconfiguration a big importance. New challenges to apply the dynamic reconfiguration at model level as well as runtime support level are required. In this direction, the development of reconfigurable DRE systems according to traditional processes is not applicable. New methods are required to build and to supply reconfigurable embedded software architectures. In this context, we propose an model‐driven engineering based approach that enables to design reconfigurable DRE systems with execution framework support. This approach leads the designer to specify step by step his/her system from a model to another one more refined until the targeted model is reached. This targeted model is related to a specific platform leading to the generation of the most part of the system implementation. We also develop a new middleware that supports reconfigurable DRE systems. Copyright © 2013 John Wiley & Sons, Ltd.